Analisa dan Implementasi Wireless Outdoor Connection Menggunakan Unifi AC Mesh Pada PT.Bandar Abadi - Muhammad Jufri; Heryanto Heryanto (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
PT. Bandar Abadi is a company engaged in shipping and ship repair with 1000 employees working there. Currently, the company still does not have and is experiencing problems in providing interconnection services that are on employee devices or CCTV installed in the outside environment. This of course disrupts employee performance due to difficulties in data transmission and CCTV control due to the network that does not cover the area. The methodology applied in this research is the NDLC (Network Development Life Cycle) method where this method functions as an infrastructure development and design that allows monitoring of the network. The results of this study are in the form of applications that can cover a large area by utilizing the Unifi AC Mesh device so that with the implementation, it can solve the problem of wireless services that exist at PT. Bandar Abadi